Physialis peruviana: BAHAN PANGAN DAN BIOAKTIVITASNYA - Marina Silalahi (LPPM Universitas Negeri Jakarta, 2018)
Physialis peruviana by the Indonesian local community call is ciplukan, which originate from Colombia and Mexico. Local communities in Indonesia use of P. peruviana as fruit and traditional medicine, so its needs studies to explain nutritional value and bioactivity. This article was written based on a study of scientific articles published online or off line. Physialis peruviana is a source of potassium, provitamin A, vitamin C, iron, and several vitamin B-complexes. In traditional medicine, the P. Peruviana is used to cure chickenpox, anti-hypertension, cancer, leukemia, hepatitis, rheumatism, antispasmodics, diuretics, antiseptics, sedatives, and analgesics. Based on the biessay, the P. peruvina has activity as anti diabetes mellitus, antioxidant, anti cancer, and anti bacterial. Compounds of 4b-Hydroxywithanolide (4bHWE), withanolides, and physangulidines A-C from P. peruviana is compounds that have the activity of inhibiting cancer cell growth through apostosis.